Quantitative determination of related substances for Lamotrigine extended release tablet by RP-HPLC - Priyanka Gondhale-Karpe; Sonali Manwatkar (Heliyon, 2023)
Lamotrigine extended release tablet dosage form LAMICTAL XR used as an anticonvulsant in the treatment of generalized tonic clonic, absence seizures and partial seizures. The objective of the present study is to develop and validate analytical method for the estimation of related substances in the LAMICTAL XR from GSK; however it is very important to have simple, sensitive, robust and validated analytical method. Hence a precise RP-HPLC analytical method developed for the determination of Related substances in LAMICTAL XR tablet dosage form with gradient elution pattern having mobile phase A as buffer pH 8.0 and mobile phase B as an Acetonitrile at 1.5 mL/min flowrate, using Hypersil BDS C18 column, ambient column temperature and PDA detector with wavelength 220 nm. The analytical method is validated as per ICH guidelines including its forced degradation studies. The method was found to be linear in the range of 0.2 ppm to 2.5 ppm with correlation coefficient 0.999. Accuracy performed at LOQ to 250% level and recovery was found to be in the range of 95% to 105%. Therefore the developed related substances method provides a safe, easy and reproducible for the stability studies and QC release testing for the estimation of related substances.